Abū Bakr ibn Abī Shaibah (235) as a Figure on the Field of Hadith | أبو بكر بن أبي شيبة (345 هـ) شخصية حديثية - Muhammad Khairul Mustaghfirin (Fakultas Dirasat Islamiyah, Univitas Islam Negeri (UIN) Syarif Hidayatullah Jakarta, 2014)
Abdullāh b. Muhammad b. Abī Shaibah al-Kūfī (d 235 AH), was a famous ḥāfiẓ(memorizer of hadith). He received the hadith from Abu al-Aḥwaş al-Ḥanafī, Sharīk al-Nakhaʻī, Hushaim b. Bashīr, Wakīʻ b. al-Jarrāḥ, Ibn Uyainah, Ibn Mahdī, Yaḥyā b. Saʻīdal-Qațțān and others. Among those who received the hadith from him are al-Bukhārī,Muslim, Abū Dāwud and Ibn Mājah. Among those who narrated hadith to him throughAhmad are al-Nasāʻī, Ahmad b. Ḥanbal, Abu Zurʻah, Abu Ḥātim. The scholars agreedthat Abū Bakr b. Abī Shaibah is person who has strong memorizing, he praised by manyscholars. Abū al-Ubaid al-Qāsim said,